Pakistan : the political economy of rural development - Karamat, Ali. (Lahore Pakistan : Vanguard Publication Ltd., 1986)
The important question to be explored and which has been discussed at some length, in the essays included in this book, is, what are the social benefits and costs of agricultural modernization in Pakistan.
Includes Index.
aia 06/04/2017
Loans
Keywords: Agriculture and state------ Pakistan; Agriculture---Economic aspects---Pakistan; Rural Development----Pakistan